(3GdJdhK HGdeHjOGJ GdcjejGhjI hCaVd GdMdhds - (3YHO GdgGOj(B, (3MSfs ((3OeTb(B:s (3OGQ YdGA GdOjf ddfTQ hGdJhRjY(B,s, 2001)
(3JUfja GdeHjOGJ(B- (3GdCKQ GdeJHbi ddehGO GdcjejGhjI(B- (3CKQ GdJdhK GdcjejGhj Ydi GdJQHI hGdCMjGA(B- (3JdhK GdeRQhYGJ HGdCSeOI GdCRhJjI(B- (3Jchf XGgQI GdebGheI hGdefGYI(B- (3GdESJgdGc GdYGdej(B- (3GdJSee HGdeHjOGJ hWQb GdRQGYI GdYVhjI(B- (3GdeHjOGJ GdeefhYIs
Keywords: (3JdhK GdHjFIs; (3MeGjI GdHjFIs